CITRAAN GERAK PADA KUMPULAN SAJAK LUPUT KARYA IDRUS TINTIN - Mohd.Adhli '; Syafrial '; Elmustian ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: Through research and discussion that has been done can be formulated conclusion that the motion images at set Sajak Escape K. Tintin works used by the author in a poem entitled "Life Kian Interest" found 11 images of motion. In the poem titled "In the Storm" found 12 images of motion. In the poem titled "Poem Black" found 3 images of motion. In the poem titled "Heart" diremukan 1 motion imagery. In the poem titled "Diary of A sailor found 5 motion imagery. In the poem titled "Notes A man" found 8 images of motion. In the poem titled "Message A Father To His son" found 1 images of motion. In the poem titled "Spirit" found 5 of motion imagery. In the poem titled "I wrote Hope" found 4 images of motion. In the poem titled "War" found 1 images of motion. In the poem titled "Dimension" is found first motion imagery. Motion imagery most commonly found in the poem "In the Storm" which contained 12 images of motion. The least motion imagery is found in the poem "War", "Heart", and "Dimension" which is found only 1 motion imagery. Of the total of all the poems discussed are found as many as 52 images of motion. In the poem Escape set